"Big bang" nào cho hệ thống tài chính Việt Nam hiện nay - Ngô, Đăng Thành (ĐHQGHN, 2017)
In the past, there were some huge change in the finacial system of England and Japan, which called “BIG BANG" in financial sector (England is the first in 1986, and Japan is the second in 1996). They, England and Japan, had to creat such “BIG BANG” in order to reform their financial structure to catch up with the world economy. Vietnam has different status with them but also has same target: to catch up with the globalization finacial system. So, there is a hint that Vietnam can creat another “Big Bang” to reduce the time in joining the area and world financial system. The way to create “Big Bang” in Vietnam’s finanacial system should be: liberalizes the goverment bonds; aparts the Central Bank from Ministry of Financials control; re-structure the commercial banking system; build and launch the Law of ownership, firstly the land ownership;...